A "resistance calculator": Simple stewardship intervention for refining empiric practices of antimicrobials in acute-care hospitals. (19th September 2021) - Zilberman-Itskovich, Shani; Strul, Nathan; Chedid, Khalil; Martin, Emily T.; Shorbaje, Akram; Vitkon-Barkay, Itzhak; Marcus, Gil; Michaeli, Leah; Broide, Mor; Yekutiel, Matar; Zohar, Yarden; Razin, Hadas; et al.
Abstract: Objective: In the era of widespread resistance, there are 2 time points at which most empiric prescription errors occur among hospitalized adults: (1) upon admission (UA) when treating patients at risk of multidrug-resistant organisms (MDROs) and (2) during hospitalization, when treating patients at risk of extensively drug-resistant organisms (XDROs). These errors adversely influence patient outcomes and the hospital's ecology. Design and setting: Retrospective cohort study, Shamir Medical Center, Israel, 2016. Patients: Adult patients (aged >18 years) hospitalized with sepsis. Methods: Logistic regressions were used to develop predictive models for (1) MDRO UA and (2) nosocomial XDRO. Their performances on the derivation data sets, and on 7 other validation data sets, were assessed using the area under the receiver operating characteristic curve (ROC AUC). Results: In total, 4, 114 patients were included: 2, 472 patients with sepsis UA and 1, 642 with nosocomial sepsis. The MDRO UA score included 10 parameters, and with a cutoff of ≥22 points, it had an ROC AUC of 0.85. The nosocomial XDRO score included 7 parameters, and with a cutoff of ≥36 points, it had an ROC AUC of 0.87. The range of ROC AUCs for the validation data sets was 0.7–0.88 for the MDRO UA score and was 0.66–0.75 for nosocomial XDRO score. We created a free web calculator (https://assafharofe.azurewebsites.net ). Conclusions: A simple electronic calculator could aid with empiric prescription during an encounter with a septic patient. Future implementation studies are needed to evaluate its utility in improving patient outcomes and in reducing overall resistances.